A Robust Force Control Approach for Underwater Vehicle Manipulator Systems*. Issue 1 (July 2017) - Heshmati-alamdari, Shahab; Nikou, Alexandros; Kyriakopoulos, Kostas J.; Dimarogonas, Dimos V.
Abstract: In various interaction tasks using Underwater Vehicle Manipulator Systems (UVMSs) (e.g. sampling of the sea organisms, underwater welding), important factors such as: i) uncertainties and complexity of UVMS dynamic model ii) external disturbances (e.g. sea currents and waves) iii) imperfection and noises of measuring sensors iv) steady state performance as well as v) inferior overshoot of interaction force error, should be addressed during the force control design. Motivated by the above factors, this paper presents a model-free control protocol for force controlling of an Underwater Vehicle Manipulator System which is in contact with an unknown compliant environment, without incorporating any knowledge of the UVMS's dynamic model, exogenous disturbances and sensor's noise model. Moreover, the transient and steady state response as well as reduction of overshooting force error are solely determined by certain designer-specified performance functions and are fully decoupled by the UVMS's dynamic model, the control gain selection, as well as the initial conditions. Finally, a simulation study clarifies the proposed method and verifies its efficiency.